Dynamics of nanostructured light emitted diodes - Chan, CCS (2014)
Experimental investigations of the optical properties of GaN nanostructured light emitting diode (LED) arrays are presented. Microphotoluminescence spectroscopy with pulsed and continuous wave lasers was used to probe the carrier dynamics and emission mechanisms of nanorod LED arrays fabricated by a top down etching method. Results show a possible reduction in internal electric field as nanorod diameter decreases. Localisation effects were also observed, affecting the spectral shape of the nanorod emission. Under two-photon excitation, quantum dot-like sharp spectral peaks in the PL spectra are found to exist in abundance amongst all the nanorod samples. The optical properties of these localised states, which are shown to be associated with the nanorod free-surfaces, are characterised using non-linear and time resolved spectroscopy. An investigation into spatially resolved single nanorods was also carried out. Single nanorods were isolated, and characterised using pulsed lasers. The etching is shown to increase the carrier decay life-time at extended intervals over several hundred ns. The temporal evolution and excitation power density dependence of the quantum dot-like states are also presented for the first time. The long lived localised states are thought to arise from surface effects, in particular Fermi-surface pinning, causing localisation and spatial separation of carriers. Additional work on nano-pyramid array LEDs, with quantum wells on semi-polar surfaces is also presented. Optical properties using micro-photoluminescence are compared to cathodoluminescence studies. An uneven distribution of emission wavelengths across the pyramid facet is thought to lead to an emission mechanism involving carriers transferring between multiple spatially localised states. Finally, experimental techniques and fabrication methods for future work are documented in detail.